Interaksi Komunikasi Umat Beragama di Daerah Mayoritas Karo - Miranda W. Lubis; Abdul Rasyid (Wardah, 2023)
This article aims to discuss the interaction of religious communication in the Karo majority area in Durin Jangak Village. Religious harmony refers to the cooperation of religious communities based on tolerance. In the experience of religious teachings, there must be mutual understanding, mutual respect, and equality. Therefore, looking at the relationship among religious people, the purpose of this research is to review more deeply how the interaction of religious communication exists in the Karo ethnic majority area in Durin Jangak Village. The In-Dept Interview data collection technique is used in a phenomenological qualitative research approach. This includes in-depth interviews with informants in the form of questions or oral conversations. The results of the study show that the communication interactions of religious communities in Durin Jangak Village, where the majority are Karo tribes, are mutual respect, non-judgmental, non-intimidating, greeting each other, accepting differences of religion and opinion, and not forgetting tolerance as a manifestation of avoiding inter-religious conflict.